Exit and Paradise Creek Fluvial Features, 2012 - Curran, Janet H. (ORCID: 000-0002-3899-6275); Williams, Haley B. (USGS Science Data Catalog, 2017)
This dataset presents delineations of the braid plains of Exit and Paradise Creeks in Kenai Fjords National Park, Alaska for 2012 conditions. A braid plain can be defined generally as the area over which a braided river shifts, and can include active braid plain (the suite of wetted channels and largely unvegetated intervening bars) and inactive braid plain (vegetated formerly occupied channels and bars still accessible by braiding without substantial bank erosion). An additional category of transitional braid plain here describes areas where vegetation is disturbed by recent sediment transport but not fully removed. Because processes are changing as Exit Glacier retreats, selected former fluvial surfaces are no longer expected to be accessible by typical braiding and may be removed from the braid plain. For 2012 conditions, inactive braid plain mapping was only conducted on Exit Creek downstream of the prominent moraines dating to the 1800s.